The Association Between Dietary Inflammatory Index and Parathyroid Hormone in Adults With/Without Chronic Kidney Disease - Qin, Zheng; Yang, Qinbo; Liao, Ruoxi; Su, Baihai (Frontiers in Nutrition, 2021)
Aims: We aimed to assess the association between dietary inflammation index (DII) with parathyroid hormone (PTH) and hyperparathyroidism (HP) in adults with/without chronic kidney disease (CKD). Methods: Data was obtained from the 2003-2006 National Health and Nutrition Examination Survey (NHANES). Participants who less than 18 years old, pregnant, missing the data of DII, PTH and CKD were excluded. DII was calculated based on a 24-h dietary recall interview for each participant. Weighted multivariable regression analysis and subgroup analysis were preformed to estimate the independent relationship between DII with PTH and HP in CKD/non-CKD population. Results: A total of 7679 participants were included with the median DII of -0.24 (-2.20 1.80) and mean PTH level of 43.42 ± 23.21 pg/mL. The average PTH was 45.53 ± 26.63 pg/mL for participants in the highest tertile compared with 41.42 ± 19.74 pg/mL in the lowest tertile group (P<0.0001). The rate of HP was 11.15% overall, while the rate in the highest DII tertile was 13.28% and 8.60% in the lowest DII tertile (P<0.0001). Participants with CKD trended to have the higher PTH levels compared to their counterparts (61.23 ± 45.62 vs 41.80 ± 19.16 pg/mL, P<0.0001). A positive association between DII scores and PTH was observed (β=0.46, 95%CI: 0.25, 0.66, P= <0.0001) and higher DII was associated with an increased risk of HP (OR=1.05, 95% CI: 1.02, 1.08, P=0.0023). Subgroup analysis results indicated that this association was similar in participants with different renal function, gender, age, BMI, hypertension and diabetes status and could also be appropriate for CKD population. Conclusions: Higher consumption of pro-inflammatory diet appeared to have higher PTH level and increased risk of HP. Anti-inflammatory dietary management maybe beneficial to reduce the risk of HP both in population with and without CKD.